(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify the effect of learning with educational scaffolds on achievement and reflective thinking among students of the Art Education Department. The researcher used the experimental design, that is, the design of two equal groups with partial control over some variables, and with a post-test (the achievement test and the reflective thinking scale), and she chose the research sample intentionally from the students of the first stage - the Department of Art Education - the College of Basic Education - Al-Mustansiriya University, and by simple random drawing, a hall was represented. (2) The experimental group, which studied according to the educational scaffolding strategy, with (28) male and female students, and (1) the control group, which studied according to the traditional method, with (28) male and female students The two research tools were determined by the achievement test in planning and colors and the test of the contemplative thinking scale. The validity and reliability of the two tools were confirmed. The researcher took into account the internal and external safety of the experiment. The researcher prepared (12) teaching plans, with (6) plans for the students of the experimental group and (6) for the students of the experimental group. The female officer.. After completing the application of the experiment, the achievement test and the reflective thinking scale were conducted, and after obtaining the data for both (test and scale) and processing them with statistical means represented by the t-test for two independent samples of equal numbers, the results were obtained, and in light of them, the researcher concluded the following:The students of the experimental group that studied according to the educational scaffolding strategy outperformed the students of the control group that studied according to the traditional method in the achievement test for planning and colors and the reflective thinking scale. The researcher recommended emphasizing the use of the educational scaffolding strategy as it is better than the traditional method in collecting planning and colors and developing contemplative thinking among first-stage students.